Plasmonic Lipid Bilayer Membranes for Enhanced Detection Sensitivity of Biolabeling Fluorophores. (31st October 2015) - Bhattacharya, Rupak; Indukuri, Chaitanya; Begam, Nafisa; Seeck, Oliver H.; Basu, Jaydeep K.
Abstract : Plasmonics based sensing, using the surface plasmon resonance of metal nanoparticles, has been effectively demonstrated in various applications. Extending this methodology to cell and artificial lipid bilayer membranes is extremely beneficial in enhancing the sensitivity of the detection of binding and cellular transport of molecules across such membranes. Here, the creation of an artificial plasmonic biomembrane template is demonstrated and used to show the enhanced detection sensitivity of certain widely used biomarker molecules. The efficacy of these templates is explained in terms of the ability of the hydrophobic polymer grafted gold nanoparticles used to organize, penetrate, and fluidize the membranes. The enhancement of photoluminescence of the dye molecules used occurs over a reasonably large spectral range as compared to the plasmon resonance of gold nanoparticles. The results could, possibly, be extended to cellular membranes with relevant modifications, as well as to the detection of any other biological molecule appropriately labeled with fluorescent dye molecules, and demonstrate the versatility of these plasmonic bioinspired platforms as potential biochemical sensors. Abstract : A novel method for ultrasensitive biomarker sensing is achieved by plasmonic bio‐membrane templates for a wide range of fluorophores. Gold nanoparticle assemblies are used on lipid bilayer to get an emission enhancement through Förster resonance energy transfer. Furthermore, the role of nanoparticle membrane binding and penetration as well as its consequence on observed enhanced bio‐fluorophore detection sensitivity is elucidated.